Interaction between Energy Consumption and Economic Growth in Pakistan: A More Comprehensive Analysis Using ARDL Approach - Khan, Oshin; Younas, Muhammad Zeeshan (Energy Economics Letters, 2019)
Energy arguably plays a substantial part in the economic growth process. In this paper, we examine the intertemporal causal relationship between energy consumption and economic growth in Pakistan during the period of 1985–2017. Unlike the majority of the previous studies, we employ the newly developed autoregressive distributed lag (ARDL)-bounds testing approach by Pesaran et al. (2001) to examine this association. It is an attempt to explore the long run ties for energy consumption and energy intensity with economic growth, urbanization, trade openness, and financial development. Results postulate that the trade openness has a positive impact on energy consumption while urbanization and financial development have a negative influence. As far as sectoral analysis is concerned, agriculture and manufacturing share has a positive imprint on energy while the services sector has a negative effect. Overall, the study finds that energy consumption spurs economic growth in Pakistan. The findings have practical policy implications for decision makers in the area of macroeconomic planning.